2005
DOI: 10.1002/hed.20136
|View full text |Cite
|
Sign up to set email alerts
|

Which classification for ethmoid malignant tumors involving the anterior skull base?

Abstract: Both the 1997 and 2002 AJCC-UICC classifications seemed to have limited prognostic value. By contrast, the INT classification satisfied one of the main goals of tumor staging, demonstrating the progressive worsening of prognosis with different tumor classes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
0
10
0
2
Order By: Relevance
“…A craniofacial resection combined with radiotherapy when necessary, has become the "gold standard" for tumours that have transgressed the anterior skull base. Several studies (Patel et al, 2003;Cantù et al, 2005) have shown a dramatic improvement of survival in patients who were considered incurable before the advent of this technique. Nevertheless, the morbidity and mortality of traditional craniofacial resection are quite high.…”
Section: Discussionmentioning
confidence: 97%
“…A craniofacial resection combined with radiotherapy when necessary, has become the "gold standard" for tumours that have transgressed the anterior skull base. Several studies (Patel et al, 2003;Cantù et al, 2005) have shown a dramatic improvement of survival in patients who were considered incurable before the advent of this technique. Nevertheless, the morbidity and mortality of traditional craniofacial resection are quite high.…”
Section: Discussionmentioning
confidence: 97%
“…We, indeed, believe that the major advantage of the endoscopic approach lies in the outstanding possibility of having a magnified visualization of the site of origin as well as of the areas involved by the tumor. [31][32][33] The largest series is a recent international collaborative study analyzing 1307 patients treated with ACFR at 17 institutions. In larger tumors the endoscopic surgeon must proceed in a step-by-step dissection (multilayer technique), usually starting with a debulking of the lesion and subsequently carrying out the dissection in a centripetal fashion starting far from areas involved by the tumor along the subperiosteal plane or by even including the underlying bone whenever at risk of involvement, with a constant progressive assessment of tumor boundaries.…”
Section: Discussionmentioning
confidence: 99%
“…Its capacities for tissue invasion, osseous lysis, and proliferation seem rather reduced compared to other malignant neoplasms of the nose and sinuses . Metastases being rare, survival is dependent on local control . For the last 20 years, the gold standard treatment was based on the sequence: surgery then radiotherapy .…”
Section: Introductionmentioning
confidence: 99%